The relation between health insurance and management of hypertension in Shanghai, China: a cross-sectional study - Xinji Zhang; Yuan Zhang; Xiang Xiao; Xiuqiang Ma; Jia He (BMC, 2016)
Abstract Background We aimed to investigate the management of hypertension in Shanghai, China and to examine whether there was any difference of hypertension management among people enrolled in different health insurances. Methods In this cross-sectional study, a total of 31,531 residents were selected in Shanghai, using a randomized, stratified, multi-stage sampling method, and were asked to provide their status of hypertension, condition of hypertension management, health insurances and other demographic information. A weighted propensity score model was used to adjust confounders and to analyze the differences on hypertension management among hypertension patients enrolled in different health insurances. Results In Shanghai, most hypertension patients achieved good management of hypertension. However, patients enrolled in the New Cooperative Medical Scheme or the Urban Resident Basic Medical Insurance scheme were more likely to achieve publicity of precautionary knowledge about hypertension (OR = 2.36 [95 % CI :1.96,2.85] and 1.28 [95 % CI:1.12,1.45], respectively) and had their blood pressure under control (OR = 1.33 [95 % CI :1.09,1.62] and 1.22 [95 % CI:1.05,1.42], respectively) than patients enrolled in the Urban Employee Basic Health Insurance scheme. Conclusion The study provided a comprehensive description of hypertension in Shanghai, China. To support the management of hypertension, publicity of hypertension prevention knowledge should be improved, especially to people enrolled in the Urban Employee Basic Health Insurance scheme.